Prevalence and Severity of Steatosis in Chronic Hepatitis C patients - Pir Muhammad Zahid, Farman Ullah Shah, Najeeb Ullah, Mohammad Hanif, Rabia Khalid, Muhammad Ibrahim Khan, Sobiya Mohiuddin Omar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hepatitis C virus infection is a worldwide health issue. The rise in the prevalence of steatosis may be attributed to alterations in eating patterns, changes in the nutritional content of food, and changes in lifestyle, such as decreased physical activity and high sedentary lifestyle, as well as etio-pathogenic variables that influence individuals from infancy. Objective: To determine prevalence and severity of steatosis in chronic hepatitis C patients Methodology: The current study was cross sectional study piloted at the Gastroenterology Department, Hayatabad Medical Complex, Peshawar. The duration of study was six months after synopsis approval from August 2021 to January 2022. Totally 200 patients fulfilling the inclusion criteria were included in our study. Under aseptic conditions, a liver biopsy was done using an 18G lumbar puncture needle. All the Data analysis was done by using IBM SPSS version 24. Results: The overall frequency of steatosis was 80 (40%). On the basis of degree of steatosis, mild steatosis was observed in 53 (58.89%) subjects, moderate steatosis in 31 (34.44%) patients while severe steatosis was observed in 6 (6.67%) subjects. Conclusion: Our study concludes that steatosis is a common histological characteristic in patients with chronic hepatitis C virus infection. Steatosis is more prevalent in female patients than males. Study based on large sample size is recommended to get better findings.